Digital skills among students of the master’s program in Palliative Care and Pain Management - Vargas Encalada, Eddie Enrique (2023)
Objective: To determine the digital skills among students of the master’s program in Palliative Care and Pain Management at Universidad Nacional Mayor de San Marcos School of Medicine in 2022.Materials and methods: A non-experimental, descriptive and cross-sectional research. The study population was comprised of students of the master’s program in Palliative Care and Pain Management enrolled in the year 2022. A non-probability sample was used. Data were collected through the survey “Digital Skills in Higher Education Questionnaire” (CDES), consisting of 46 indicators distributed in five factors with a reliability of 0.96 according to Cronbach’s alpha. Data confidentiality and participants’ autonomy were respected.Results: The final sample was made up of 59 students, the average age was 38.03 years and 76.3 % were women. All students had a personal computer and Internet access. The descriptive analysis showed that the “very important” rating prevailed: 49.2 % for the “digital citizenship” factor, 47.5 % for the “communication and collaboration” factor, 45.8 % for the “creativity and innovation” and the “access and use of information” factors, and 44.1 % for the “digital literacy” factor. According to the digital skills global analysis, 49.2 % and 42.4 % chose the “very important” and “important” ratings, respectively. There were no results for the “not at all important” rating. Conclusions: All students had a personal computer and Internet access, which confirms the growing interest in including aspects related to digital skills in university education. The “digital literacy” and the “digital citizenship” factors had a lower and higher rating, respectively, compared to the other factors. A total of 91.6 % of the students considered that digital skills are important and very important, which could be considered as highly favorable.